Chemical constituents from garcinia maingayi / lzaddin, S.A., Syuriati, N. and Rafidah, K. - S.A., lzaddin; N., Syuriati; K., Rafidah (2008)
Studies on the stem bark of Garcini maingayi have led to the isolation of two terpenoids stigmasterol 1 and sitosterol 2. The structures of these compounds were determined by spectroscopic methods such as mass spectroscopy (MS), 1H & 13 CNMR and by comparison with previous studies. These structures were isolated from hexane crude.